2018
DOI: 10.3390/ma11060921
|View full text |Cite
|
Sign up to set email alerts
|

Improving Thermo-Oxidative Stability of Nitrile Rubber Composites by Functional Graphene Oxide

Abstract: Graphene oxide (GO), modified with anti-aging agent p-phenylenediamine (PPD), was added into nitrile rubber (NBR) in order to improve the thermo-oxidative stability of NBR. The modification of GO and the transformation of functional groups were characterized by Fourier transform infrared spectroscopy (FTIR), Raman, and X-ray diffraction (XRD). Mechanical performances of NBR composites before and after the thermo-oxidative aging were recorded. The results of dynamic mechanical analysis (DMA) show an increased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…This indicated that NG could effectively inhibit the thermal oxygen aging of NBR and enable it to maintain better mechanical properties after thermal oxygen aging. In addition, from our previous work [8], GO contributes less to the improvement of aging resistance of NBR, because it agglomerates easily and cannot form an effective network structure. Besides, it does not have anti-aging groups or the ability to capture free radicals in the NBR chains during the aging process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicated that NG could effectively inhibit the thermal oxygen aging of NBR and enable it to maintain better mechanical properties after thermal oxygen aging. In addition, from our previous work [8], GO contributes less to the improvement of aging resistance of NBR, because it agglomerates easily and cannot form an effective network structure. Besides, it does not have anti-aging groups or the ability to capture free radicals in the NBR chains during the aging process.…”
Section: Resultsmentioning
confidence: 99%
“…To improve aging resistance properties, physical blending and chemical modification are deemed essential. Generally, physical blending is more popular because of its easy operation and low environmental pollution [4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first stage, the temperature corresponding to the maximum degradation rate of SSBR/PPD-GO was 10 • C higher than that of SSBR. This is because some of the free radicals generated in the thermal oxygen degradation process were captured by the amino group on PPD-GO [6]. Figure 6b showed the DSC curve of SSBR/PPD-GO.…”
Section: The Thermal Properties Of Ssbr Compositesmentioning
confidence: 99%
“…In the past decades, nanoparticles have received increasing interest owing to its unique structural and surface properties. There are many nanoparticles have been applied to improve the performances of rubber, such as graphene [5][6][7][8], layered double hydroxide [9,10], nano silica [11], carbon nano tubes [12], montmorillonite [13,14], ect. The properties of nanocomposites are better than that of conventional composites in the same composition due to the quantum effect and surface effect caused by the small…”
Section: Introductionmentioning
confidence: 99%